Validation method for extraction and determination of marbofloxacin in plasma and edible chicken tissues - Urzúa Pizarro, Natala Francisca (2018)
Marbofloxacin (MBX) is an antimicrobial for exclusive veterinary use, relatively new and of which there are few analytical methods for the extraction, identification and quantification in plasma and edible tissues (muscle, liver, kidney, lung, skin) in broiler chickens. The objective of developing a simple, sensitive and efficient extraction and detection method through highperformance liquid chromatography (HPLC) with fluorescence detection. For the preparation of the samples, known concentrations of MBX, enrofloxacin (ENX) as internal standard, methanol, water and perchloric acid, were added to plasma or tissues. Chromatographic conditions were: fluorescence detector at λex 295 and λem 490 nm, mobile phase composed of deionized water, acetonitrile and triethylamine adjusted to pH 3.0. For all matrices, the method was linear (r2 = 0.99) for MAR concentrations (0.039 to 2.5 μg/ml or gr), with an average retention time for MBX in the different matrices of 3.97 ± 0.144 minutes, and 4.99 ± 0.24 minutes for the internal standard (enrofloxacin). Detection limit in all matrices was less than 0.006 μg/ml, while recoverability percentage was 89 ± 4.65% and variation coefficients in intraday-interday assay ≤ 1.4%, determining the accuracy of the study. The analytical method applied is efficient, sensitive and reliable for future residue determinations or pharmacokinetic studies of marbofloxacin in plasma, muscle, liver, kidney, skin and lung in broiler chickens.